PEMANFAATAN GREEN HOUSE KEMBANG HARAPAN UNTUK MENINGKATKAN KEPEDULIAN LINGKUNGAN DI MI MA’ARIF GONDANG WATUMALANG - Lindi, Putri; Haryanto, Sri; Agus Faisal, Vava Imam (JISPE Journal of Islamic Primary Education, 2023)
This study aims to determine the application of the Green House program in science lessons in increasing student awareness of the environment. Green House is a controlled plant growing environment. The development of green houses for horticultural cultivation is very important as a guarantor for the success of growing from environmental influences such as temperature, air humidity, sun intensity, and pests and diseases. The use of greenhouses in plant cultivation is one way to provide an environment that is closer to the optimum conditions for plant growth. The research method used is a qualitative Field Research method, with data collection techniques carried out through observation, interviews and documentation. The analysis techniques are in the form of data collection, data reduction, data display and drawing conclusions. Researchers will search and find data broadly and in-depth regarding the method of utilizing the hope flower green house to increase environmental awareness for the upper class of MI Ma'arif Gondang Watumalang. The use of the Green House is a flower of hope to increase environmental awareness for the upper-class MI ma'arif Gondang Watumalang. The results of this study show an increase as marked by disposing of garbage in its place, picketing the yard of community service for all school residents, and sorting organic or non-organic waste.